2019
DOI: 10.3390/cancers11121854
|View full text |Cite
|
Sign up to set email alerts
|

Association of ATG4B and Phosphorylated ATG4B Proteins with Tumorigenesis and Prognosis in Oral Squamous Cell Carcinoma

Abstract: Oral squamous cell carcinoma (OSCC) is one of the major leading causes of cancer death worldwide due to the limited availability of biomarkers and therapeutic targets. Autophagy related protease 4B (ATG4B) is an essential protease for the autophagy machinery, and ATG4B phosphorylation at Ser383/392 increases its proteolytic activity. ATG4B expression and activation are crucial for cancer cell proliferation and invasion. However, the clinical relevance of ATG4B and phospho-Ser383/392-ATG4B for OSCC remains unkn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 29 publications
(50 reference statements)
1
27
0
Order By: Relevance
“…found the co-expression of higher MAP1LC3B and SQSTM1 was significantly associated with poor disease-specific survival and disease-free survival in OSCC patients ( 23 ). In addition, another tissue microarray analysis suggested that ATG4B, an autophagy related protease, could be a potential biomarker for diagnosis and prognosis for OSCC ( 24 ). To date, studies using large-scale expression patterns of ARGs to screen and develop molecular biomarkers and prognostic gene signature for OSCC are still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…found the co-expression of higher MAP1LC3B and SQSTM1 was significantly associated with poor disease-specific survival and disease-free survival in OSCC patients ( 23 ). In addition, another tissue microarray analysis suggested that ATG4B, an autophagy related protease, could be a potential biomarker for diagnosis and prognosis for OSCC ( 24 ). To date, studies using large-scale expression patterns of ARGs to screen and develop molecular biomarkers and prognostic gene signature for OSCC are still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…More than 90% of oral cancers are oral squamous cell carcinoma (OSCC) which is typically observed on the tongue, buccal mucosa and lips [1]. Cigarette smoking, alcohol drinking, betel quid chewing, chronic periodontitis [2] and viral infections [3] are major risk factors contributing to the incidence of OSCC.…”
Section: Introductionmentioning
confidence: 99%
“…ATG4B activity is required for cell cycle progression 34 and the protein levels of ATG4B and phosphorylated ATG4B (S383/392) is highly associated with tumor progression in cancer patients 35,36 . Thus, ATG4B inhibitor is expected to have suppressive effects in cancer cells.…”
Section: Development Of Atg Protein Inhibitors For Cancer Therapymentioning
confidence: 99%